Risk Factors For The Occurrence of Low Birth Weight Based on Nutritional Status of Pregnant Women With Upper Arm Circumference - Suci Saftari Apriani; Ranti Lestari; Elizabeth Widayati; Yani Suryani; Karlina Angga P (Journal of Midwifery, 2021)
The nutritional status of pregnant women before and during pregnancy can affect the growth of the fetus in the womb. The purpose of this study was to look at the risk factors of  LBW events based on nutritional status based on the MUAC size of pregnant women. This research is analytical with cross sectional study design by sampling using the total sampling technique of 98 pregnant women in Kubang Village, Sukaresmi District, Cianjur Regency. Analyze data using Chi Square. Univariate analysis results from 98 respondents have good nutritional status (MUAC≥23.5 cm) which is as much as 78 (80%) and normal birth weight 64 (65.3%) pregnant women. The results of bivariate analysis there is a meaningful relationship between the nutritional status of pregnant women based on LBW and the incidence of LBW value P value = 0.006 (P value<0.05). In conclusion there is a meaningful relationship between the nutritional status of pregnant women based on MUAC and the incidence of LBW value P value = 0.006 (P value<0.05) value (OR=3.345, CI 2.234-8.562), respondents who have a history of malnutrition status while pregnant have a risk of 3,354 times giving birth to babies with LBW